2012
DOI: 10.1063/1.3682062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an externally attached neutrally buoyant transmitter on mortal injury during simulated hydroturbine passage

Abstract: On their seaward migration, juvenile salmonids commonly pass hydroelectric dams. Fish passing through hydroturbines experience a rapid decrease in pressure as they pass by the turbine blade. The severity of this decompression can be highly variable but can result in injuries such as swim bladder rupture, exophthalmia, and emboli and hemorrhaging in the fins and tissues. Recent research indicates that the presence of a telemetry tag (acoustic, radio, inductive) implanted inside the coelom of a juvenile salmon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Carlson et al (2012) demonstrated that for juvenile Chinook Salmon exposed to rapid decompression associated with simulated turbine passage, the probability of injury and mortality increased as tag burden increased. To overcome this, we recommend using the smallest tag possible to minimize tag burden or a neutrally buoyant, externally attached tag (tag burden of 0%; Deng et al 2012;Janak et al 2012;Brown et al 2012dBrown et al , 2013b, when examining survival of fish exposed to rapid decompression associated with infrastructure passage. In addition, having a telemetry transmitter inside the body cavity may limit the amount that a swim bladder can expand before it ruptures or causes compression-related injuries.…”
Section: Field Validation Of Modeled Mortality Relationshipsmentioning
confidence: 99%
“…Carlson et al (2012) demonstrated that for juvenile Chinook Salmon exposed to rapid decompression associated with simulated turbine passage, the probability of injury and mortality increased as tag burden increased. To overcome this, we recommend using the smallest tag possible to minimize tag burden or a neutrally buoyant, externally attached tag (tag burden of 0%; Deng et al 2012;Janak et al 2012;Brown et al 2012dBrown et al , 2013b, when examining survival of fish exposed to rapid decompression associated with infrastructure passage. In addition, having a telemetry transmitter inside the body cavity may limit the amount that a swim bladder can expand before it ruptures or causes compression-related injuries.…”
Section: Field Validation Of Modeled Mortality Relationshipsmentioning
confidence: 99%
“…However, the authors also state that this may be attributed to elevated stress and subsequent infection associated with confinement in the hatchery pond [35]. Brown et al [81] compared survival of externally tagged hatchery-reared Chinook salmon juveniles during simulated turbine passage (laboratory) and found no difference in mortality between tagged and control fish. A further (field) comparison between surgically implanted (PIT-tags) and externally tagged hatchery-reared Chinook smolts during passage of hydropower stations and along river reaches showed that external tags were suitable for short-term migration studies, but not for longer periods than 10 days due to tag loss and mortality [40].…”
Section: Survivalmentioning
confidence: 99%
“…Results of previous laboratory research suggest that the use of a neutrally buoyant externally attached tag may alleviate the bias encountered in turbine-passage survival studies when using internal tags (e.g., [7], [14], [15]) and this field research suggests that carrying an externally attached transmitter may not increase predation compared to carrying an internally implanted transmitter during such studies. Many aging turbines in the Lower Snake and Columbia river dams will soon be replaced with turbines designed for safer fish passage.…”
Section: Discussionmentioning
confidence: 85%
“…The fork length (FL; mm) and mass (g) of each fish were measured before being assigned to a surgeon and tag type. For external attachment of tags, fish were placed on a foam rubber pad and oriented dorsal side up (for detailed methods and images of tags, see [7], [15]). The neutrally buoyant acoustic transmitters were attached to the dorsal musculature anterior to the dorsal fin by two simple interrupted sutures (Monocryl 5-0 absorbable monofilament) using 2×2×2×2 reinforced square knots (similar to Deters et al [25]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation